An updated checklist of Nepticulidae (Lepidoptera) of the Crimea, Sub-Mediterranean SE Europe - Navickaitė, Asta; Diškus, Arūnas; Stonis, Jonas R. (Zootaxa, 2014)
This updated checklist is intended to be a collaborative effort by a team of taxonomists to present a hitherto little known diversity of the Nepticulidae of the Crimea. A total of 64 species of Nepticulidae are listed. The following 26 species are recorded for the first time from the Crimea: Stigmella confusella (Wood & Walsingham, 1894), S. tiliae (Frey, 1856), S. microtheriella (Stainton, 1854), S. alnetella (Stainton, 1854), S. glutinosae (Stainton, 1858), S. desperatella (Frey, 1856), S. torminalis (Wood, 1890), S. crataegella (Klimesch, 1936), S. hahniella (Wörz, 1937), S. catharticella (Stainton, 1853), S. malella (Stainton, 1854), S. rhamnella (Herrich-Schäffter, 1860), S. ulmivora (Fologne, 1860), S. trimaculella (Haworth, 1828), S. obliquella (Heinemann, 1862), S. tityrella (Stainton, 1854), S. carpinella (Heinemann, 1862), S. lemniscella (Zeller, 1839), S. plagicolella (Stainton, 1854), S. samiatella (Zeller, 1939), Bohemannia pulverosella (Stainton, 1849), Ectoedemia mahalebella (Klimesch, 1936), Fomoria septembrella (Stainton, 1849), Trifurcula silviae van Nieukerken, 1990, T. macedonica Z. Laštůvka & A. Laštůvka, 1998, T. eurema (Tutt, 1899). One species, Ectoedemia spinosella (Joannis, 1908), is excluded here from the list of the Nepticulidae of the Crimea. Thirty-nine selected species are illustrated with photographs of the leaf-mines, and forty-five species with photographs of genitalia.